2016
DOI: 10.1152/ajprenal.00562.2015
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory peptide Ac-SDKP is released from thymosin-β4 by renal meprin-α and prolyl oligopeptidase

Abstract: The anti-inflammatory peptide Ac-SDKP is released from thymosin-␤4 by renal meprin-␣ and prolyl oligopeptidase. Am J Physiol Renal Physiol 310: F1026 -F1034, 2016. First published March 9, 2016 doi:10.1152/ajprenal.00562.2015.-N-acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP) is a natural tetrapeptide with antiinflammatory and antifibrotic properties. Previously, we have shown that prolyl oligopeptidase (POP) is involved in the Ac-SDKP release from thymosin-␤4 (T␤4). However, POP can only hydrolyze peptides sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 45 publications
0
53
0
Order By: Relevance
“…Clinical studies involving ACE inhibitor therapy have shown increased plasma and tissue Ac‐SDKP concentrations, and some of the beneficial effects of ACE inhibitors in fibrotic diseases are attributable, in part, to increased Ac‐SDKP content (Kumar & Yin, ). It has been reported that Tβ4 is hydrolysed by meprin α and prolyl oligopeptidase, and meprin α knockout mice exhibited a significantly lower basal amount of Ac‐SDKP than wild‐type mice (Kumar et al., ). In the present study, we found that exogenous Ac‐SDKP attenuated silicosis in rats or in fibroblasts induced by Ang II, owing to activation of the ACE2–Ang‐(1–7)–AT 1 pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies involving ACE inhibitor therapy have shown increased plasma and tissue Ac‐SDKP concentrations, and some of the beneficial effects of ACE inhibitors in fibrotic diseases are attributable, in part, to increased Ac‐SDKP content (Kumar & Yin, ). It has been reported that Tβ4 is hydrolysed by meprin α and prolyl oligopeptidase, and meprin α knockout mice exhibited a significantly lower basal amount of Ac‐SDKP than wild‐type mice (Kumar et al., ). In the present study, we found that exogenous Ac‐SDKP attenuated silicosis in rats or in fibroblasts induced by Ang II, owing to activation of the ACE2–Ang‐(1–7)–AT 1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP), an antifibrotic peptide, can be cleaved by the N-terminal of ACE (Masuyer, Douglas, Sturrock, & Acharya, 2015) and released from thymosin 4 (T 4), hydrolysed by meprin and prolyl oligopeptidase (Kumar et al, 2016). Ac-SDKP has been proved to attenuate lung fibrosis in silicotic rats (Xu et al, 2012) or in mice treated with bleomycin (Conte et al, 2016).…”
mentioning
confidence: 99%
“…Kumar et al. focused on the biology of POP. POP can cleave the peptide that is shorter than the sequence of 30 amino acids.…”
Section: Acsdkp Synthesismentioning
confidence: 99%
“…However, Tβ4 is indeed 43 amino acids; therefore, theoretically, an additional enzymatic cleavage process should be required. Kumar et al . clearly showed that meprin‐α is a potential responsible enzyme to cleave Tβ4 and subsequently enable POP to cleave Tβ4 fragments to synthesize AcSDKP.…”
Section: Acsdkp Synthesismentioning
confidence: 99%
“…Prosaposin-derived 18-mer peptide (PS18: LSELIIN-NATEELLIKGL) protected against Ab 1-42 -induced neurotoxicity via activation of the caspase pathway (Gao et al, 2016;Table 2). N-acetyl-serylaspartyl-lysylproline (Ac-SDKP) is a natural tetrapeptide with antiinflammatory and antifibrotic properties and it is released from thymosin-b4 by renal meprin-a and prolyl oligopeptidase (Kumar et al, 2016). Ac-SDKP facilitated hippocampal neurogenesis mediated by VEGF via the PI3K/GSK-3b/b-catenin signalling pathways (Kim et al, 2015; Table 2).…”
Section: Artificially Designed Biomimetic Peptidesmentioning
confidence: 99%